2015
DOI: 10.1016/j.ram.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of canine zoonotic enteroparasites in Bahía Blanca, Argentina

Abstract: The objectives of this research were: (1) to determine the occurrence of zoonotic enteroparasites in dog feces from Bahía Blanca, Argentina; (2) to characterize the spatial distribution of the parasites found in association with the quality of life index (QLI) in neighborhoods of Bahía Blanca; and (3) to determine if the presence of a particular parasite genus in a stool sample was facilitated or impeded by the presence of other parasite genera. Samples of dog stools (n=475) were collected between December 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 41 publications
7
15
0
5
Order By: Relevance
“…The most prevalent species were A. caninum , U. stenocephala , T. vulpis and T. canis . Other studies indicated similar results regarding the presence of these parasites in other countries (Bwalya et al., ; Letra Mateus, Castro, Ribeiro, & Vieira‐Pinto, ) and in other localities of Argentina (La Sala et al., ; Semenas et al., ). It is important to note that these parasite species previously mentioned are widely known as potential agents of zoonosis.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The most prevalent species were A. caninum , U. stenocephala , T. vulpis and T. canis . Other studies indicated similar results regarding the presence of these parasites in other countries (Bwalya et al., ; Letra Mateus, Castro, Ribeiro, & Vieira‐Pinto, ) and in other localities of Argentina (La Sala et al., ; Semenas et al., ). It is important to note that these parasite species previously mentioned are widely known as potential agents of zoonosis.…”
Section: Discussionsupporting
confidence: 64%
“…Several studies were carried out to determine the prevalence of intestinal parasites in dogs in other countries, with different results (Amissah‐Reynolds et al., ; Zanzani et al., ). In Argentina, heterogeneous values of prevalence in dogs were reported by different authors (36.6%–69.8%) (Dopchiz et al., ; La Sala et al., ; Soriano et al., ). In this study, high prevalence of enteroparasitosis in dogs (82.1%) gave account of great canine faecal contamination and deficient health care of pets, which can affect both animal and human sanitation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results were in agreement with other studies in different parts of the world, such as Bahía Blanca of Argentina that indicated 14.7% of dogs were infected with Cryptosporidium spp. (9). The results of the current study showed that the frequency of Cryptosporidium spp.…”
Section: Discussionsupporting
confidence: 45%
“…Domestic dogs (Canis lupus familiaris) are generally considered as the first domesticated mammal from very early in human history (about 12,000 years ago) and are the most abundant species of carnivore around the world today, whoch are the definitive or reservoir hosts of more than 60 zoonotic parasites, such as Cryptosporidium spp. (8)(9)(10). Therefore, they are a real problem in public health for humans, particularly in villages and poorly marginalized communities of towns.…”
Section: Introductionmentioning
confidence: 99%